2009
DOI: 10.1534/genetics.109.104935
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Genomic Predictions Across Multiple Populations

Abstract: Genomic prediction of future phenotypes or genetic merit using dense SNP genotypes can be used for prediction of disease risk, forensics, and genomic selection of livestock and domesticated plant species. The reliability of genomic predictions is their squared correlation with the true genetic merit and indicates the proportion of the genetic variance that is explained. As reliability relies heavily on the number of phenotypes, combining data sets from multiple populations may be attractive as a way to increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
305
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(335 citation statements)
references
References 30 publications
26
305
2
2
Order By: Relevance
“…Therefore it is recommended to exclude such families from the TS. This finding is also in agreement with a simulation study showing that increasing accuracies by combining different populations into a single TS requires persistence of marker-QTL LD across populations (de Roos et al 2009). …”
Section: Influence Of Ts Compositionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore it is recommended to exclude such families from the TS. This finding is also in agreement with a simulation study showing that increasing accuracies by combining different populations into a single TS requires persistence of marker-QTL LD across populations (de Roos et al 2009). …”
Section: Influence Of Ts Compositionsupporting
confidence: 91%
“…Therefore it is recommended to exclude such families from the TS. This finding is also in agreement with a simulation study showing that increasing accuracies by combining different populations into a single TS requires persistence of marker-QTL LD across populations (de Roos et al 2009). The strong correlation (0.89 , r , 0.93) among s IBS , s GC , and s LP suggests that any of these measures can be used to estimate genetic similarity between populations to identify populations with negative predictive signal.…”
supporting
confidence: 91%
“…Since prediction of GEBVs is shown to be more reliable when juvenile animals share their recent pedigree with animals in the reference population (Habier et al, 2007), it seems straightforward that composing a reference population closely related to the juvenile selection candidates is an optimal strategy. De Roos et al (2008a), however, showed, that it is particularly important that at least some of the animals in the reference population originate from the same pedigree or line as the juvenile animals. This indicates that a reference population that needs to serve multiple lines may optimally contain animals from all lines, and yield nearly as accurate predictions for each of the lines as a line-specific reference population may do.…”
Section: Genomic Prediction -The Processmentioning
confidence: 99%
“…Further, 20 000 females and 300 males from the last historical generation were used as founders. Similar strategies (shrinkage and expansion of the population) have been used in simulations of dairy cattle populations (De Roos et al, 2009;Habier et al, 2009).…”
Section: Simulationsmentioning
confidence: 99%